Environmental immune disruptors, inflammation and cancer risk - Thompson, Patricia A.; Khatami, Mahin; Baglole, Carolyn J.; Sun, Jun; Harris, Shelley A.; Moon, Eun-Yi; Al-Mulla, Fahd; Al-Temaimi, Rabeah; Brown, Dustin G.; Colacci, Anna Maria; Mondello, Chiara; Raju, Jayadev; et al. (Carcinogenesis (New York), 2015)
An emerging area in environmental toxicology is the role that chemicals and chemical mixtures have on the cells of the human immune system. This is an important area of research that has been most widely pursued in relation to autoimmune diseases and allergy/asthma as opposed to cancer causation. This is despite the well-recognized role that innate and adaptive immunity play as essential factors in tumorigenesis. Here, we review the role that the innate immune cells of inflammatory responses play in tumorigenesis. Focus is placed on the molecules and pathways that have been mechanistically linked with tumor-associated inflammation. Within the context of chemically induced disturbances in immune function as co-factors in carcinogenesis, the evidence linking environmental toxicant exposures with perturbation in the balance between pro- and anti-inflammatory responses is reviewed. Reported effects of bisphenol A, atrazine, phthalates and other common toxicants on molecular and cellular targets involved in tumor-associated inflammation (e.g. cyclooxygenase/prostaglandin E2, nuclear factor kappa B, nitric oxide synthesis, cytokines and chemokines) are presented as example chemically mediated target molecule perturbations relevant to cancer. Commentary on areas of additional research including the need for innovation and integration of systems biology approaches to the study of environmental exposures and cancer causation are presented.